Knowledge Management and The Role of Management Accountants on The Company's Sustainable Reputation - Christina Dwi Astuti; Etty Murwaningsari; Yvonne Augustine Sudibyo (Journal of Social Science, 2022)
This research aims to analyze the influence of knowledge management and the role of management accountants on the company’s sustainable reputatiob. The knowledge management variable is measured by 13 statement items divided into 3 dimensions (sharing, storing, learning), the role of management accountants with 11 statements divided into 2 dimensions (strategic, conventional), and the reputation of a sustainable company as many as 24 statement items divided into 3 dimensions (product & innovation, governance & workplace, leadership & performance). This research uses quantitative methods with the analysis unit is the manager at the lowest to highest level in Indonesia, especially in Indonesia. The sampling technique used is purposive sampling. The data was collected by distributing questionnaires, of which only 245 questionnaires could be processed. Data is processed using SEM analysis using AMOS version 22. The results showed that variable knowledge management has a positive influence on the company's reputation variables while the management accountant role variable has no influence on the company's reputation.